Code-Mixing And Language Play in Threads: Constructing Digital Persona of Indonesian Game Streamers - Virginio, Gabriel Aditya; Betari, Asa Wisesa; Pramono, Satrio Aji (Inspiring: English Education Journal, 2025)
In the dynamic landscape of digital communication, bilingual expression has become an essential tool for online identity construction, especially among content creators in the gaming community. Despite increasing interest in social media discourse, limited attention has been paid to the linguistic strategies used by Indonesian game streamers on social media platforms. This study aims to explore the use of code mixing and language play in shaping digital personas through the public posts of three popular Indonesian streamers on Threads. Using a qualitative method, 90 purposively selected posts were analysed to identify code-mixing types, communicative functions, and creative language patterns. The study found that insertion and alternation were the most frequent code-mixing strategies, used to express emotion, share information, and maintain social connection. Each streamer demonstrated distinct language play styles, ranging from humorous exaggeration to brand-oriented clarity. These linguistic choices contribute to authenticity, audience engagement, and identity signalling. The study underscores how bilingual creativity operates as a social and aesthetic practice in digital youth culture.